(untitled) (International Journal of Built Environment and Sustainability, 2019)
Development within the construction industry shows that higher education is critical in the sector’s skills improvement. However, research findings are also explicit about absent and shadow integration of core sustainable construction modules for built environment’s curricula. The study aimed to examine issues critical for the integration of sustainability element in the built environment curricula. It outlined two objectives which: (1) to determine the causes for the low integration of sustainability elements in academic curricula and, (2) to identify the principal factors inhibiting the integration of sustainability elements in academic curricula in Nigeria. Data for the study was obtained using a questionnaire survey administered to a random sample of 186 academic stakeholders related to schools of the built environment across Nigeria with factor analysis was subsequently employed to analyze the survey data. The results showed that seven principal factors inhibit and are responsible for the dearth of sustainable construction modules in built environment academic curricula in Nigeria. These are: (1) Skills and knowledge dearth, (2) Lack of empowerment to effect change, (3) Low level of awareness, (4) Lack of green building council, (5) Lack of real-life sustainable projects, (6) Non-prioritization by accreditation bodies and (7) Lack of research and industry collaboration. The findings suggest that strong government policy and viable industry and academic collaboration are imperative to effect curriculum change in support of the integration of sustainability element in the built environment curricula. The findings reported in this paper is significant as a basis to inaugurate the development of academic curricula which integrates the sustainability elements, capable of driving behavioural change to adapt sustainability practices among graduates.